A New Model for Nowcasting the Aviation Radiation Environment With Comparisons to In Situ Measurements During GLEs - A. D. P. Hands; F. Lei; C. S. Davis; B. J. Clewer; C. S. Dyer; K. A. Ryden (Space Weather)
Abstract Significant increases to the atmospheric radiation environment are recorded by a network of ground level neutron monitors as ground level enhancements (GLEs). These space weather phenomena pose a risk to aviation via single event effects in aircraft electronics and ionizing dose to passengers and crew. Under the UK Space Weather Instrumentation, Measurement, Modeling and Risk programme, we have developed a new model to provide nowcasts of the aviation radiation environment, including both the galactic cosmic ray (GCR) background and during GLE events. The Model for Atmospheric Ionising Radiation Effects (MAIRE+) uses multiple data sources to characterize primary GCR and GLE particle spectra and combines these with precalculated geomagnetic and atmospheric response matrices to predict particle fluxes from ground level to 20 km altitude across the entire globe. Two European neutron monitors (located at Oulu in Finland and Dourbes in Belgium) are used as the primary indicators of GLE intensity in order to maximize accuracy over UK airspace. Outputs from MAIRE+ for the historical GLEs in September and October 1989 are compared to recalibrated empirical data from a solid‐state detector that was carried on Concorde in that period. The model will be hosted in the UK and will provide additional capability to the Met Office Space Weather Operations Center (MOSWOC).